2020
DOI: 10.1055/s-0040-1713063
|View full text |Cite
|
Sign up to set email alerts
|

Current Trends of Dermatophytosis in Eastern Odisha

Abstract: Background Dermatophytes are fungi parasitizing structures rich in keratin such as skin, hair, and nail, which leads to a dermal inflammatory response with intense itching and cosmetic disfigurement. The climatic condition of eastern India is predominantly hot and humid with severe rainfalls promoting fungal infection. This study was performed to determine the prevalence of dermatophytosis and to isolate and identify the dermatophyte from clinically suspected cases attending tertiary care center. Methodology T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
1
4
2
1
Order By: Relevance
“…However, this finding is in contrast to other studies who reported tinea corporis, 21 tinea capitis 29 and tinea cruris 30 as the commonest clinical manifestations than tinea unguium. Tinea capitis is the second most common form of tinea and accounted 24.1% of all dermatomycosis.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, this finding is in contrast to other studies who reported tinea corporis, 21 tinea capitis 29 and tinea cruris 30 as the commonest clinical manifestations than tinea unguium. Tinea capitis is the second most common form of tinea and accounted 24.1% of all dermatomycosis.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, the maceration of periungual tissue caused by the use of manicure tools can result cross-infection among people who use this service. 27,28 However, this finding is in contrast to other studies who reported tinea corporis, 21 tinea capitis 29 and tinea cruris 30 as the commonest clinical manifestations than tinea unguium. Tinea capitis is the second most common form of tinea and accounted 24.1% of all dermatomycosis.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…Antifungal susceptibility studies should be performed as increased and prolonged use of antifungal agents has led to the development of resistance. 9 In our study, the maximum number of subjects were found in the age groups of 21-30 and 31-40 years (37.3% and 22.7% respectively). Similar findings have been noted in studies done by Basak et al, 10 the maximum cases of dermatophytoses were seen in the age group of 21-30 years (25.4%) followed by age group of 31-40 years (20.3%), Walke HR et al, 11 Poluri et al, 12 the highest incidence of dermatophytosis was observed in the age group of 21-40 years, Yadav et al, 13 dermatophytosis was more common in the age group of 21-30 years (30%) followed by 31-40 years (23%), Mishra M 14 and Sen and Raul.…”
Section: Discussionsupporting
confidence: 45%
“…[ 11 22 ] According to some recent studies T. mentagrophytes or interdigitale is more commonly isolated than T. rubrum , indicating a shift in the etiological agent. [ 23 ] However, another study from North India reported T. rubrum as the most common isolate (46.4%). [ 24 ] In our study, none of the samples grew T. rubrum .…”
Section: Discussionmentioning
confidence: 99%